Cytokeratins in epithelia of odontogenic neoplasms - Crivelini, Marcelo Macedo [UNESP]; De Araújo, V. C.; De Sousa, S. O. M.; De Araújo, N. S. (Wiley, 2003)
Neoplasms and tumours related to the odontogenic apparatus may be composed only of epithelial tissue or epithelial tissue associated with odontogenic ectomesenchyme. The immunohistochemical detection of different cytokeratins (CKs) polypeptides and vimentin has made it easier to explain the histogenesis of many epithelial diseases. The present study aimed to describe the immunohistochemical expression of cytokeratins 7, 8, 10, 13, 14, 18, 19 and vimentin in the epithelial components of the dental germ and of five types of odontogenic tumours. The results were compared and histogenesis discussed. All cells of the dental germ were positive for CK14, except for the preameloblasts and secreting ameloblasts, in which CK14 was gradually replaced by CK19. CK7 was especially expressed in the cells of the Hertwig root sheath and the stellate reticulum. The dental lamina was the only structure to express CK13. The reduced epithelium of the enamel organ contained CK14 and occasionally CK13. Cells similar to the stellate reticulum, present in the ameloblastoma and in the ameloblastic fibroma, were positive for CK13, which indicates a nature other than that of the stellate reticulum of the normal dental germ. The expression of CK14 and the ultrastructural aspects of the adenomatoid odontogenic tumour probably indicated its origin in the reduced dental epithelium. Calcifying odontogenic epithelial tumour is thought to be composed of primordial cells due to the expression of vimentin. Odontomas exhibited an immunohistochemical profile similar to that of the dental germ. In conclusion, the typical IF of odontogenic epithelium was CK14, while CK8, 10 and 18 were absent. Cytokeratins 13 and 19 labelled squamous differentiation or epithelial cells near the surface epithelium, and CK7 had variable expression.
Keywords: Immunohistochemistry; Neoplasms; Odontogenic neoplasms; cytokeratin; cytokeratin 10; cytokeratin 13; cytokeratin 14; cytokeratin 18; cytokeratin 19; cytokeratin 7; cytokeratin 8; unclassified drug; vimentin; ameloblast; ameloblastoma; cell differentiation; cell ultrastructure; epithelium; fibroma; histogenesis; human; human tissue; immunohistochemistry; odontogenic tumor; priority journal; protein expression; squamous cell carcinoma; tooth flora; tumor calcinosis; Ameloblastoma; Connective Tissue; Enamel Organ; Epithelial Cells; Humans; Intermediate Filaments; Keratin-10; Keratin-14; Keratin-7; Keratin-8; Keratins; Odontogenic Tumors; Odontoma; Tooth Germ; Vimentin